2011
DOI: 10.1002/rbf.14
|View full text |Cite
|
Sign up to set email alerts
|

Dividends, Momentum, and Macroeconomic Variables as Determinants of the US Equity Premium Across Economic Regimes

Abstract: The equity premium of the S&P 500 Index is explained in this paper by several variables that can be grouped into fundamental, behavioral and macroeconomic factors. We hypothesize that the statistical significance of these variables changes across economic regimes. The three regimes we consider are the low, medium and high volatility regimes in contrast to previous studies that do not differentiate across economic regimes. Using the three-state Markov switching regime econometric methodology we confirm that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…At the same time, numerous studies analyzed the relationships between macroeconomic variables and stock market indices using GARCH volatility time-series models (Bhar and Malliaris, 2011;Chen, 2009;Erdem et al, 2005;Hanousek and Kocenda, 2011;Hsing, 2011;Hsing and Hsieh, 2012;Kim et al, 2004;Nguyen, 2011;Rangel, 2011). Also, the results indicated that the conditional volatility of macroeconomic variables significantly influence stock market indices.…”
Section: Review Of Previous Empirical Studiesmentioning
confidence: 99%
“…At the same time, numerous studies analyzed the relationships between macroeconomic variables and stock market indices using GARCH volatility time-series models (Bhar and Malliaris, 2011;Chen, 2009;Erdem et al, 2005;Hanousek and Kocenda, 2011;Hsing, 2011;Hsing and Hsieh, 2012;Kim et al, 2004;Nguyen, 2011;Rangel, 2011). Also, the results indicated that the conditional volatility of macroeconomic variables significantly influence stock market indices.…”
Section: Review Of Previous Empirical Studiesmentioning
confidence: 99%
“…Foerster (2011) evaluates the performance of momentum traders who buy stocks which have recently doubled in price in anticipation of further future gains and find that this strategy led to predictable disappointment. Malliaris and Bhar (2011) studied the role of momentum in equity premium puzzle across economic regimes using modeling and three-state Markov switching regime econometric methodology. On the behavioral end, role of disposition on momentum traders (Kubińska et al , 2012) and, on the demographic end, cross-country cultural difference affecting momentum returns (Chui et al , 2010) have also been studied.…”
Section: Behavioral Finance Indicators At the Aggregate Level – Does Rationality Exist?: Contradictory Evidencementioning
confidence: 99%